2002
DOI: 10.1007/s00572-002-0187-4
|View full text |Cite
|
Sign up to set email alerts
|

Morphological types of arbuscular mycorrhizal fungi in roots of understory plants in Japanese deciduous broadleaved forests

Abstract: Morphological types of arbuscular mycorrhizal (AM) fungi in roots of understorey plants were examined in three different Japanese deciduous broadleaved forests. In total, 43 species belonging to 33 genera from 27 families were examined for the morphological types of AM. The number of flowering plant species having Paris-type AM was greater than those having Arum-type AM in each plot. This tendency was more prominent in herbaceous plants than woody plants with nine species having Paris-type associations among t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
28
1
1

Year Published

2004
2004
2017
2017

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 69 publications
(33 citation statements)
references
References 24 publications
2
28
1
1
Order By: Relevance
“…This variation of the Paris-type mycorrhizas has also been described by Gerdemann [33] and Bedini et al [9]. The Paris-type was seen to be dominant in the herbaceous understory plants of the NOA, similar results were found by Yamato and Iwasaki [85] for herbaceous plants of the forests of the Kansai region. These facts indicate that the Paris-type is advantageous for herbaceous understory plants that grow slowly with low light intensity and low nutrient availability levels.…”
Section: Discussionsupporting
confidence: 86%
“…This variation of the Paris-type mycorrhizas has also been described by Gerdemann [33] and Bedini et al [9]. The Paris-type was seen to be dominant in the herbaceous understory plants of the NOA, similar results were found by Yamato and Iwasaki [85] for herbaceous plants of the forests of the Kansai region. These facts indicate that the Paris-type is advantageous for herbaceous understory plants that grow slowly with low light intensity and low nutrient availability levels.…”
Section: Discussionsupporting
confidence: 86%
“…As estruturas fúngicas do tipo "Paris" estariam associadas às espécies de etapas sucessionais tardias (Zangaro et al, 2008), tolerantes à sombra e de crescimento lento (Yamato & Iwasaki, 2002). A predominância da morfologia tipo "Arum" em A. colubrina var.…”
Section: Discussionunclassified
“…Brundrett & Kendrick (1990) indicated that the presence or absence of intercellular air spaces in the root cortical region to be an important determinant of AM morphology. Later studies elaborated this view and speculated the influence of factors like light, moisture and temperature of the substrates on AM patterns in roots as these factors can influence root growth (Yamato & Iwasaki 2002;Yamato 2004;Becerra et al 2007). However, detailed studies exploring root anatomy of lithophytic plant species, especially the intercellular spaces in roots could reveal their contribution to AM morphology.…”
Section: Am Morphologymentioning
confidence: 99%